Stød and syllabicity in a Jutlandic dialect - Molbæk Hansen, Peter (Annual Report of the Institute of Phonetics University of Copenhagen, 1978)
The paper is concerned with the Himmerlandic dialect in North East Jutland. Certain phonological structures which are ambiguous with regard to occurrence of syllabicity, namely long vocoids and certain sequences of sonorant segments, are discussed. It is argued - on the basis of certain prosodic phenomena (the behaviour of stød and stress) - that from a functional point of view these structures are best described as disyllabic. A brief discussion of the possible connection between the Jutlandic apocope and the behaviour of these structures is given.